Pengembangan Laboratorium Virtual Fisika Osilasi - Rizal, Adhi; Adam, Riza Ibnu; Susilawati, Susilawati (JOIN (Jurnal Online Informatika), 2018)
This research aims to develop a virtual lab application with oscillation concept. Oscillation concept in this application is described as pendulum motion. The application was developed by using the ADDIE model and Easy Java Simulations (EJSs) software. It has advantages compared with similar applications, which has a damping coefficient that similar with real world condition. Some other features of the application are the users can run and pause the simulation, observe the details of changes in pendulum movement angle by using step forward button, users can change pendulum mass, adjust the length of the rope, gravitational force, initial angle, damping coefficient, and can observe the change of pendulum angular position in parabolic graphs in real-time. The application was tested using the Technology Acceptance Model (TAM) concept. Based on the research results, the user satisfaction level is categorized as very useful. Therefore, it can be conclude that the application can be accepted and used well by the user.